Effect of the combined application of rhizobacteria and compost on the ability of Pteris vittata L. as a phytoremediator for mercury in gold mine tailing - Aminatun, Tien; Budiwati, Budiwati; Suhartini, Suhartini; Raharjo, Rahmanto (Brawijaya University, 2026)
Artisanal gold mining activities in Indonesia often cause mercury (Hg) pollution, which is toxic and bioaccumulative. Phytoremediation using Pteris vittata L. as a hyperaccumulator and rhizobacteria Pseudomonas aeruginosa RTKP1 is an alternative to overcome this problem. This study aimed to analyze the effect of combined treatment of Pseudomonas aeruginosa RTKP1 induction and compost on the ability of Pteris vittata L. to accumulate Hg in gold mine tailings. The treatment consisted of bacterial induction without compost, and with compost at a tailings:compost ratios of 1:1 and 2:1. This study used descriptive and quantitative analyses. The results showed that Pseudomonas aeruginosa RTKP1 induction without compost resulted in the highest reduction in Hg levels in the tailings, from 10.7 mg/kg to 0.00467 mg/kg with a medium-high BCF value and TF <1, indicating a phytostabilization mechanism. However, the addition of compost reduced the effectiveness of bioaccumulation. Hence, treatment of Pseudomonas aeruginosa RTKP1 without compost was most effective in increasing the ability of Pteris vittata L. to reduce mercury content.